PENGEMBANGAN ALAT UJI KOMPONEN ELEKTRONIKA DASAR BERBASIS ARDUINO ATMEGA 2560 - Aditya, Mufti; Dwi Ananda, Dimas (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
The advancement of electronic technology requires the availability of supporting tools that can test components quickly and accurately. One common problem encountered in the field is the difficulty in identifying the working value of components such as Zener diodes due to faded markings or labels on the component body. Additionally, testing basic components, such as regular diodes, capacitors, SCRs, and transistors, is still often done manually, which is an inefficient process. Therefore, this final project aims to design and develop a basic electronic component testing device based on a microcontroller, which is capable of detecting the condition of components and displaying the test results automatically and informatively. The method used in this project includes the stages of design, assembly, and programming using the Arduino ATmega2560. The tool is equipped with two 20x4 I2C LCDs; one is dedicated to displaying the working voltage of Zener diodes, while the other displays the status of other components such as diodes, SCRs, transistors (NPN and PNP), and capacitors. The system operates by utilizing a B25 voltage sensor and the voltage divider principle to detect the working values of each component. The test results indicate that this device accurately displays the Zener diode’s working voltage with an average error of less than 10%. Furthermore, the tool can identify the condition of other components with valid and consistent results.